A Fuzzy Collaborative Sensor Network for Semiconductor Manufacturing Cycle Time Forecasting. (31st March 2013) - Lin, Yu-Cheng; Chen, Toly; Wang, Yu-Cheng
Abstract : Network based sensing has become an important field of research, and it is expected that new applications of remote sensing will be developed. A fuzzy collaborative sensor network is developed in this study to predict the cycle time of a job in a semiconductor manufacturing factory, which is an important task for the factory. In the fuzzy collaborative sensor network, each sensor detects the status of a particular job as well as various environmental conditions present in the factory and uses a fuzzy neural network to analyze the received information. Each sensor communicates its settings and forecasting results to other sensors with the aid of a central control unit. According to the experimental results, the aggregate forecasting performance was considerably improved through the sensors' collaboration.